Epoxy resin forming material as well as preparation method and application thereof
By adjusting the component content and proportions in the epoxy resin molding material, a material with high continuous mold formation stability was prepared, which solved the problem of short mold cleaning cycle of plastic sealing materials in the prior art, achieved stable continuous mold formation in the semiconductor packaging process, and improved production efficiency and product stability.
Patent Information
- Application Number
- CN202411955273.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the mold clearing cycle of plastic sealing materials is short, which leads to the inability to work stably for a long time and cannot meet the stable continuous molding requirements of semiconductor packaging materials in production.
An epoxy resin molding material is provided, and its components include 6-9.5% by weight of epoxy resin, 2-5.5% by weight of the first curing agent, 80-86% by weight of solid filler, 0.2-0.5% by weight of ion trapping agent, 0.5-0.8% by weight of low stress modifier, 0.2-0.8% by weight of coupling agent, 0.1-0.3% by weight of curing agent, 2-5% by weight of the decomposition, 1-2% by weight of flame retardant and 0.1-0.5% by weight of colorant. By adjusting the content and proportion of these components, a material with high continuous mold formation stability is prepared.
通过使用该环氧树脂成型材料,能够显著提高半导体芯片封装过程中的连续成模稳定性,延长清模周期,降低不良率,提高生产效率和产品稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of epoxy resin materials, and in particular to an epoxy resin molding material and a preparation method and application thereof. Background Art
[0002] With the rapid development of 5G technology, the application scenarios and application environments of electronic products have become more diversified, and the performance requirements for semiconductor packaging materials have become higher and higher. In addition to having certain mechanical properties to prevent semiconductor chips from being damaged by the external environment, they are also required to have stable continuous moldability in packaging production. In addition to improving production efficiency and reducing costs, stable continuous moldability can also improve product stability and reduce defective rates. The current way to improve continuous moldability is generally to match the wax system between the plastic encapsulation material and the mold clearing glue to avoid mold contamination caused by incompatibility between different wax systems during the packaging process. However, it is easy to cause a short mold clearing cycle of the plastic encapsulation material. A short mold clearing cycle will increase the frequency of mold clearing, resulting in an inability to work stably for a long time. Summary of the invention
[0003] The purpose of the present invention is to overcome the problem of short mold clearing cycle of plastic encapsulation material in the prior art and inability to work stably for a long time, and to provide an epoxy resin molding material and its preparation method and application. The epoxy resin molding material prepared according to the method of the present invention has high continuous molding stability.
[0004] In order to achieve the above object, the present invention provides an epoxy resin molding material on the one hand, which contains, based on the total weight of the epoxy resin molding material, 6-9.5% by weight of epoxy resin, 2-5.5% by weight of a first curing agent, 80-86% by weight of a solid filler, 0.2-0.5% by weight of an ion capture agent, 0.5-0.8% by weight of a low stress modifier, 0.2-0.8% by weight of a coupling agent, 0.1-0.3% by weight of a curing accelerator, 2-5% by weight of a chemical, 1-2% by weight of a flame retardant and 0.1 -0.5 wt % of colorant; wherein the chemical material is prepared by melt mixing a second curing agent, an antioxidant and a release agent under an inert atmosphere, and based on the total weight of the chemical material, the chemical material contains 70-85 wt % of the second curing agent, 5-15 wt % of the antioxidant and 5-15 wt % of the release agent; the first curing agent is a combination of linear phenolic resin and XYLOK phenolic resin, the second curing agent is linear phenolic resin, the antioxidant is a phenolic antioxidant and / or an amine antioxidant, and the release agent is polyethylene wax and / or monoglyceride wax.
[0005] Preferably, based on the total weight of the epoxy resin molding material, the epoxy resin molding material contains 6.5-9 weight % of epoxy resin, 2-4.5 weight % of a first curing agent, 80-85 weight % of a solid filler, 0.2-0.4 weight % of an ion capture agent, 0.5-0.7 weight % of a low stress modifier, 0.2-0.6 weight % of a coupling agent, 0.15-0.3 weight % of a curing accelerator, 2.5-4.5 weight % of a chemical material, 1.5-2 weight % of a flame retardant and 0.2-0.5 weight % of a colorant.
[0006] Preferably, based on the total weight of the chemical material, the chemical material contains 75-85 wt % of the second curing agent, 7-15 wt % of the antioxidant and 7-15 wt % of the release agent.
[0007] Preferably, in the first curing agent, the mass ratio of the linear phenolic resin to the XYLOK phenolic resin is 1-3:1.
[0008] Preferably, the solid filler is a combination of crystalline silica and fused silica.
[0009] Preferably, the mass ratio of the crystalline silica to the molten silica is 8-15:1.
[0010] Preferably, the curing accelerator is triphenylphosphine and / or 2-phenyl-4-methylimidazole.
[0011] Preferably, the epoxy resin is o-cresol-formaldehyde epoxy resin and / or dicyclopentadiene epoxy resin.
[0012] Preferably, the ion capture agent is at least one of an anion capture agent, a cation capture agent, an anion-cation capture agent and a hydrotalcite compound.
[0013] Preferably, the low stress modifier is at least one of an organosilicon-modified epoxy resin, a silicone resin, and a triblock copolymer containing an organosilicon component.
[0014] Preferably, the coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane.
[0015] Preferably, the flame retardant is at least one of a halogen flame retardant, a halogen-free flame retardant, a phosphorus flame retardant, a nitrogen flame retardant and a hydroxide flame retardant.
[0016] Preferably, the colorant is carbon black.
[0017] A second aspect of the present invention provides a method for preparing the epoxy resin molding material described above, the method comprising the following steps: (1) Under an inert atmosphere, melt-mixing a second curing agent, an antioxidant and a release agent to obtain a chemical material; (2) Melting and kneading the chemical material with epoxy resin, a first curing agent, a solid filler, an ion scavenger, a low stress modifier, a coupling agent, a curing accelerator, a flame retardant and a colorant.
[0018] Preferably, in step (1), the melt mixing conditions include: temperature of 150-170° C. and time of 30-120 min.
[0019] Preferably, in step (2), the melt mixing conditions include: temperature of 75-85°C and time of 7-9 min.
[0020] The third aspect of the present invention provides the use of the epoxy resin molding material mentioned above in a semiconductor chip packaging process.
[0021] According to the technical solution of the present invention, by adjusting the content, type and proportion of epoxy resin, first curing agent, solid filler, ion capture agent, low stress modifier, coupling agent, curing accelerator, chemical material, flame retardant and colorant, an epoxy resin molding material with higher continuous molding stability can be obtained. DETAILED DESCRIPTION
[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The epoxy resin molding material of the present invention contains, based on the total weight of the epoxy resin molding material, 6-9.5 wt % of epoxy resin, 2-5.5 wt % of a first curing agent, 80-86 wt % of a solid filler, 0.2-0.5 wt % of an ion capture agent, 0.5-0.8 wt % of a low stress modifier, 0.2-0.8 wt % of a coupling agent, 0.1-0.3 wt % of a curing accelerator, 2-5 wt % of a chemical material, 1-2 wt % of a flame retardant and 0.1-0.5 wt % of a colorant; The chemical material is prepared by melt-mixing a second curing agent, an antioxidant and a mold release agent under an inert atmosphere, and based on the total weight of the chemical material, the chemical material contains 70-85% by weight of the second curing agent, 5-15% by weight of the antioxidant and 5-15% by weight of the mold release agent; The first curing agent is a combination of linear phenolic resin and XYLOK phenolic resin, the second curing agent is linear phenolic resin, the antioxidant is a phenolic antioxidant and / or an amine antioxidant, and the release agent is polyethylene wax and / or monoglycerol wax.
[0025] In the epoxy resin molding material described in the present invention, in a preferred case, based on the total weight of the epoxy resin molding material, the epoxy resin molding material contains 6.5-9 weight % of epoxy resin, 2-4.5 weight % of a first curing agent, 80-85 weight % of a solid filler, 0.2-0.4 weight % of an ion capture agent, 0.5-0.7 weight % of a low stress modifier, 0.2-0.6 weight % of a coupling agent, 0.15-0.3 weight % of a curing accelerator, 2.5-4.5 weight % of a chemical material, 1.5-2 weight % of a flame retardant and 0.2-0.5 weight % of a colorant.
[0026] In the epoxy resin molding material of the present invention, preferably, based on the total weight of the chemical material, the chemical material contains 75-85 wt % of the second curing agent, 7-15 wt % of the antioxidant and 7-15 wt % of the release agent.
[0027] In the epoxy resin molding material of the present invention, the first curing agent is a combination of a linear phenolic resin and a XYLOK phenolic resin. In a preferred case, the mass ratio of the linear phenolic resin to the XYLOK phenolic resin is 1-3:1. The linear phenolic resin can be purchased from Jinan Shengquan Group Co., Ltd., with a brand name of PF-8011. The XYLOK phenolic resin can be purchased from Hunan Jiashengde Materials Technology Co., Ltd., with a brand name of MEH7800SS.
[0028] In the epoxy resin molding material of the present invention, the second curing agent is a linear phenolic resin, which can be purchased from Jinan Shengquan Group Co., Ltd. with a brand name of PF-8011.
[0029] In the epoxy resin molding material of the present invention, the antioxidant is a phenolic antioxidant and / or an amine antioxidant. In a specific embodiment, the phenolic antioxidant may be tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol. The amine antioxidant may be p-phenylenediamine. In the most preferred embodiment, the antioxidant is tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol. The tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol can be purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0030] In the epoxy resin molding material of the present invention, the mold release agent is polyethylene wax and / or monoglycerol wax. In the most preferred embodiment, the mold release agent is a mixture of polyethylene wax and monoglycerol wax. When the mold release agent is a mixture of polyethylene wax and monoglycerol wax, the mass ratio of the polyethylene wax to the monoglycerol wax is preferably 0.5-3:1, more preferably 1-2:1.
[0031] In the epoxy resin molding material described in the present invention, the solid filler can be at least one of crystalline silica, molten silica, metal hydroxide and metal nitride. In a preferred case, the solid filler is a combination of crystalline silica and molten silica. Further preferably, the mass ratio of the crystalline silica to the molten silica is 8-15:1, more preferably 9-12:1. The crystalline silica can be purchased from Jiangsu Lianrui New Materials Co., Ltd., with the brand name DC1270B. The molten silica can be purchased from Jiangsu Lianrui New Materials Co., Ltd., with the brand name DQ-1200.
[0032] In the epoxy resin molding material of the present invention, the curing accelerator may be triphenylphosphine and / or 2-phenyl-4-methylimidazole. In a preferred case, the curing accelerator is a combination of triphenylphosphine and 2-phenyl-4-methylimidazole. Further preferably, the mass ratio of the triphenylphosphine to the 2-phenyl-4-methylimidazole is 0.5-2:1. The triphenylphosphine can be purchased from Hangzhou Ruike Chemical Co., Ltd. under the brand name TPP. The 2-phenyl-4-methylimidazole can be purchased from Nanjing Lanbian Biochemical Technology Co., Ltd.
[0033] In the epoxy resin molding material of the present invention, the epoxy resin can be o-cresol type epoxy resin and / or dicyclopentadiene type epoxy resin. In the most preferred embodiment, the epoxy resin is o-cresol type epoxy resin. The o-cresol type epoxy resin can be purchased from Jinan Shengquan Group Co., Ltd., with the brand SQCN700-3. The dicyclopentadiene type epoxy resin can be purchased from Taiji New Materials Co., Ltd., with the brand HP7200.
[0034] In the epoxy resin molding material of the present invention, the ion capture agent can be at least one of an anion capture agent, a cation capture agent, an anion-cation capture agent and a hydrotalcite compound. In the most preferred embodiment, the ion capture agent is a hydrotalcite compound. Specifically, the hydrotalcite compound is a magnesium aluminum carbonate type hydrotalcite.
[0035] In the epoxy resin molding material of the present invention, the low stress modifier can be at least one of silicone-modified epoxy resin, silicone resin and triblock copolymer containing silicone component. In the most preferred embodiment, the low stress modifier is silicone-modified epoxy resin. The silicone-modified epoxy resin can be purchased from Shanghai Bohuai Chemical Co., Ltd., with the brand name W35.
[0036] In the epoxy resin molding material of the present invention, the coupling agent can be at least one of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane. In the most preferred embodiment, the coupling agent is γ-mercaptopropyltrimethoxysilane. The γ-mercaptopropyltrimethoxysilane can be purchased from Danyang Duoli New Materials Co., Ltd., with a brand name of KH590.
[0037] In the epoxy resin molding material of the present invention, the flame retardant may be at least one of a halogen flame retardant, a halogen-free flame retardant, a phosphorus flame retardant, a nitrogen flame retardant and a hydroxide flame retardant. Specifically, the halogen flame retardant may be brominated epoxy and / or antimony trioxide. The halogen-free flame retardant may be a metal hydroxide and / or zinc borate. The phosphorus flame retardant may be hexaphenoxy cyclotriphosphazene. The hydroxide flame retardant may be aluminum hydroxide and / or magnesium hydroxide. In the most preferred embodiment, the flame retardant is zinc borate.
[0038] In the epoxy resin molding material of the present invention, the colorant can be a conventional colorant in the art. In some embodiments, the colorant is carbon black.
[0039] The preparation method of the above epoxy resin molding material may include the following steps: (1) Under an inert atmosphere, melt-mixing a second curing agent, an antioxidant and a release agent to obtain a chemical material; (2) Melting and kneading the chemical material with epoxy resin, a first curing agent, a solid filler, an ion scavenger, a low stress modifier, a coupling agent, a curing accelerator, a flame retardant and a colorant.
[0040] In step (1), the melt mixing conditions may include: a temperature of 150-170° C., preferably 155-165° C.; and a time of 30-120 min, preferably 40-100 min.
[0041] In step (1), the inert atmosphere can be provided by an inert gas and / or nitrogen. In the most preferred embodiment, the inert atmosphere is provided by nitrogen.
[0042] In step (1), the melt mixing process is carried out under stirring. The stirring time may be 1-1.5 hours.
[0043] In step (2), the melt-kneading conditions may include: a temperature of 75-85°C and a time of 7-9 minutes. In a preferred embodiment, the melt-kneading conditions include: a temperature of 76-82°C and a time of 7.5-8.5 minutes.
[0044] The present invention also provides application of the epoxy resin molding material in a semiconductor chip packaging process.
[0045] In a specific application process, after 700 consecutive encapsulations of the epoxy resin molding material of the present invention during semiconductor chip packaging, the surface of the product still remains uniform.
[0046] The following examples further illustrate the epoxy resin molding material and its preparation method and application of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0047] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0048] In the following examples and comparative examples, the sources of the experimental materials used are as follows: o-cresol-formaldehyde epoxy resin, purchased from Jinan Shengquan Group Co., Ltd., brand SQCN700-3; Dicyclopentadiene epoxy resin, purchased from Taiji New Materials Co., Ltd., brand HP7200; Linear phenolic resin, purchased from Jinan Shengquan Group Co., Ltd., brand PF-8011; XYLOK phenolic resin, purchased from Hunan Jiashengde Material Technology Co., Ltd., brand MEH7800SS; Crystalline silica, purchased from Jiangsu Lianrui New Materials Co., Ltd., brand DC1270B; Fused silica, purchased from Jiangsu Lianrui New Materials Co., Ltd., brand DQ-1200; Triphenylphosphine, purchased from Hangzhou Ruike Chemical Co., Ltd., brand name TPP; 2-Phenyl-4-methylimidazole was purchased from Nanjing Lanbi'an Biochemical Technology Co., Ltd.; Silicone-modified epoxy resin, purchased from Shanghai Bohuai Chemical Co., Ltd., brand W35; γ-Mercaptopropyltrimethoxysilane, purchased from Danyang Duoli New Materials Co., Ltd., brand name KH590; Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with the brand number P750268.
[0049] In the following examples and comparative examples, the relevant parameters of the epoxy resin molding material were tested according to the following methods: Gelation time test: Heat the electric hot plate to 175±1℃, take 2-3g of sample and place it on the iron plate, stir it continuously with a small needle, and test the time it takes for the sample to change from fluid to gel.
[0050] Fluidity test: Take 30g sample and test it with a resin transfer injection molding machine using a spiral flow metal mold. The injection pressure is 70kgf / cm 2 , the mold temperature is 175±1℃.
[0051] Water absorption test: The water absorption test is carried out according to the "PCT24" method, where the sample size is 50mm×3mm (diameter×thickness), and the test conditions are as follows: temperature is 121°C, humidity is 100RH%, pressure is 2atm, and time is 24h; the water absorption calculation method is as follows: weight increase of the sample after "PCT24" test / initial weight of the sample×100%.
[0052] Open mold bending strength and open mold bending modulus: Take 110g of powdered epoxy resin molding material and put it into the injection molding machine. Under the conditions of injection pressure of 60bar and injection time of 15s, inject the material into a special bending strength test mold at 175℃ to make a 15.41mm×10.78mm×120mm sample. After 120s of curing, the resin product is hardened and formed. Within 15s, quickly take out the heat-cured molded sample and place it in the test area of the universal testing machine, and start the pressure test.
[0053] Glass transition temperature (Tg) and storage modulus test: The Tg of epoxy resin molding materials can be measured by dynamic mechanical analyzer (DMA) or thermomechanical analyzer (TMA), and the storage modulus is measured by DMA. First, the sample powder is cured for 150 seconds at a mold temperature of 180°C on a molding machine to make a sample strip / sheet, and then placed in an oven at 180°C for post-curing for 6 hours. The size of the sample block for TMA testing is 5mm×5mm (diameter×thickness); the size of the sample strip for DMA testing is 60mm×13mm×3.2mm (length×width×thickness).
[0054] Thermal expansion coefficient (CTE1 / CTE2) test: measured using a thermomechanical analyzer (TMA).
[0055] Continuous molding stability test: Take 16mm×11mm epoxy resin molding material cake and inject it at a pressure of 75kg / cm 2 , mold clamping pressure is 160kg / cm 2 , and the mold closing time is 120s, and continuous packaging is performed. The surface of the semiconductor device is observed until irregular color difference or dirt appears on the surface, and the number of continuous packaging molds is recorded to characterize the stability of continuous molding.
[0056] Preparation Example 1 100 g of linear phenolic resin (second curing agent) was weighed and placed in a reaction kettle at a temperature of 160° C., and nitrogen was introduced at the same time. After the linear phenolic resin was completely melted, 12 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 12 g of a release agent (containing 6 g of polyethylene wax and 6 g of monoglyceride wax) were added in sequence under stirring, and the mixture was stirred and mixed for 60 minutes to obtain chemical material X1.
[0057] Preparation Example 2 100 g of linear phenolic resin (second curing agent) was weighed and placed in a reaction kettle at a temperature of 150° C., and nitrogen was introduced at the same time. After the linear phenolic resin was completely melted, 12 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 8 g of a release agent (containing 4 g of polyethylene wax and 4 g of monoglyceride wax) were added in sequence under stirring, and the mixture was stirred and mixed for 90 minutes to obtain chemical material X2.
[0058] Preparation Example 3 100 g of linear phenolic resin (second curing agent) was weighed and placed in a reaction kettle at a temperature of 170° C. Nitrogen was introduced at the same time. After the linear phenolic resin was completely melted, 8 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 12 g of a release agent (containing 6 g of polyethylene wax and 6 g of monoglyceride wax) were added in sequence under stirring, and the mixture was stirred and mixed for 70 minutes to obtain chemical material X3.
[0059] Preparation Example 4 100 g of linear phenolic resin (second curing agent) was weighed and placed in a reaction kettle at a temperature of 160° C., and argon gas was introduced at the same time. After the linear phenolic resin was completely melted, 8 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 12 g of a release agent (containing 6 g of polyethylene wax and 6 g of monoglyceride wax) were added in sequence under stirring, and the mixture was stirred and mixed for 60 minutes to obtain chemical material X4.
[0060] Comparative Preparation Example 1 The chemical material DX1 was prepared according to the method of Preparation Example 1, except that nitrogen was not introduced into the reaction kettle.
[0061] Comparative Preparation Example 2 The chemical material was prepared according to the method of Preparation Example 1, except that the antioxidant was replaced by phosphite, thereby preparing chemical material DX2.
[0062] Example 1 9 g of o-cresol-formaldehyde epoxy resin, 1.7 g of linear phenolic resin, 0.8 g of XYLOK phenolic resin, 75 g of crystalline silica, 7.05 g of molten silica, 0.07 g of triphenylphosphine, 0.13 g of 2-phenyl-4-methylimidazole, 0.6 g of silicone-modified epoxy resin, 0.4 g of γ-mercaptopropyltrimethoxysilane, 1.2 g of zinc borate, 0.3 g of carbon black, 0.25 g of magnesium aluminum carbonate-type hydrotalcite and 3.5 g of chemical material X1 were melt-kneaded at 80° C. for 8 min and then cooled and molded to obtain the epoxy resin molding material A1 of the present invention.
[0063] The epoxy resin molding material A1 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 24s, the fluidity is 53cm, the water absorption is 0.23%, the mold opening strength is 46.42MPa, the mold opening modulus is 668Pa, the glass transition temperature (Tg) is 152℃, the linear expansion coefficient ɑ1 is 14ppm, the linear expansion coefficient ɑ2 is 52ppm, the DMA modulus at 25℃ is 11722MPa, the DMA modulus at 175℃ is 1779MPa, the DMA modulus at 260℃ is 964MPa, and the continuous molding stability is 730 molds.
[0064] Example 2 4.5 g of o-cresol epoxy resin, 1.5 g of dicyclopentadiene epoxy resin, 1.4 g of linear phenolic resin, 0.8 g of XYLOK phenolic resin, 79 g of crystalline silica, 7 g of molten silica, 0.05 g of triphenylphosphine, 0.05 g of 2-phenyl-4-methylimidazole, 0.8 g of silicone-modified epoxy resin, 0.2 g of γ-mercaptopropyltrimethoxysilane, 1 g of zinc borate, 0.4 g of carbon black, 0.5 g of magnesium aluminum carbonate hydrotalcite and 2.8 g of chemical material X1 were melt-kneaded at 80° C. for 8 min and then cooled and molded to obtain the epoxy resin molding material A2 of the present invention.
[0065] The epoxy resin molding material A2 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 26s, the fluidity is 53cm, the water absorption is 0.25%, the mold opening strength is 42.88MPa, the mold opening modulus is 653Pa, the glass transition temperature (Tg) is 148℃, the linear expansion coefficient ɑ1 is 13ppm, the linear expansion coefficient ɑ2 is 53ppm, the DMA modulus at 25℃ is 10705MPa, the DMA modulus at 175℃ is 1661MPa, the DMA modulus at 260℃ is 909MPa, and the continuous molding stability is 725 molds.
[0066] Example 3 4 g of o-cresol epoxy resin, 4 g of dicyclopentadiene epoxy resin, 1.2 g of linear phenolic resin, 1.1 g of XYLOK phenolic resin, 76 g of crystalline silica, 7 g of molten silica, 0.1 g of 2-phenyl-4-methylimidazole, 0.5 g of silicone-modified epoxy resin, 0.6 g of γ-mercaptopropyltrimethoxysilane, 1 g of zinc borate, 0.1 g of carbon black, 0.2 g of magnesium aluminum carbonate hydrotalcite and 4.2 g of chemical material X1 were melt-kneaded at 80° C. for 8 min and then cooled to obtain the epoxy resin molding material A3 of the present invention.
[0067] The epoxy resin molding material A3 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 25s, the fluidity is 55cm, the water absorption is 0.23%, the mold opening strength is 41.53MPa, the mold opening modulus is 656Pa, the glass transition temperature (Tg) is 156℃, the linear expansion coefficient ɑ1 is 14ppm, the linear expansion coefficient ɑ2 is 52ppm, the DMA modulus at 25℃ is 11220MPa, the DMA modulus at 175℃ is 1683MPa, the DMA modulus at 260℃ is 869MPa, and the continuous molding stability is 735 molds.
[0068] Example 4 The epoxy resin molding material was prepared according to the method of Example 1, except that the amounts of linear phenolic resin and XYLOK phenolic resin were adjusted to 0.5 g and 2 g, respectively, to obtain the epoxy resin molding material A4 of the present invention.
[0069] The epoxy resin molding material A4 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 25s, the fluidity is 60cm, the water absorption is 0.22%, the mold opening strength is 41.28MPa, the mold opening modulus is 642Pa, the glass transition temperature (Tg) is 151℃, the linear expansion coefficient ɑ1 is 13ppm, the linear expansion coefficient ɑ2 is 50ppm, the DMA modulus at 25℃ is 11278MPa, the DMA modulus at 175℃ is 1559MPa, the DMA modulus at 260℃ is 871MPa, and the continuous molding stability is 703 molds.
[0070] Example 5 An epoxy resin molding material was prepared according to the method of Example 1, except that the amounts of crystalline silica and molten silica were adjusted to 55 g and 27.05 g, respectively, to obtain epoxy resin molding material A5 of the present invention.
[0071] The epoxy resin molding material A5 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 26s, the fluidity is 57cm, the water absorption is 0.25%, the mold opening strength is 42.31MPa, the mold opening modulus is 650Pa, the glass transition temperature (Tg) is 150℃, the linear expansion coefficient ɑ1 is 13ppm, the linear expansion coefficient ɑ2 is 51ppm, the DMA modulus at 25℃ is 10576MPa, the DMA modulus at 175℃ is 1602MPa, the DMA modulus at 260℃ is 856MPa, and the continuous molding stability is 709 molds.
[0072] Example 6 The epoxy resin molding material was prepared according to the method of Example 1, except that the chemical material X1 was replaced by the chemical material X2, to obtain the epoxy resin molding material A6 of the present invention.
[0073] The epoxy resin molding material A6 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 26s, the fluidity is 60cm, the water absorption is 0.24%, the mold opening strength is 43.47MPa, the mold opening modulus is 666Pa, the glass transition temperature (Tg) is 154℃, the linear expansion coefficient ɑ1 is 12ppm, the linear expansion coefficient ɑ2 is 51ppm, the DMA modulus at 25℃ is 11344MPa, the DMA modulus at 175℃ is 1664MPa, the DMA modulus at 260℃ is 878MPa, and the continuous molding stability is 720 molds.
[0074] Example 7 The epoxy resin molding material was prepared according to the method of Example 1, except that the chemical material X1 was replaced by the chemical material X3, to obtain the epoxy resin molding material A7 of the present invention.
[0075] The epoxy resin molding material A7 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 25s, the fluidity is 50cm, the water absorption is 0.23%, the mold opening strength is 47.22MPa, the mold opening modulus is 669Pa, the glass transition temperature (Tg) is 152℃, the linear expansion coefficient ɑ1 is 13ppm, the linear expansion coefficient ɑ2 is 56ppm, the DMA modulus at 25℃ is 10837MPa, the DMA modulus at 175℃ is 1572MPa, the DMA modulus at 260℃ is 830MPa, and the continuous molding stability is 700 molds.
[0076] Example 8 The epoxy resin molding material was prepared according to the method of Example 1, except that the chemical material X1 was replaced by the chemical material X4, to obtain the epoxy resin molding material A8 of the present invention.
[0077] The epoxy resin molding material A8 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 27s, the fluidity is 55cm, the water absorption is 0.25%, the mold opening strength is 40.60MPa, the mold opening modulus is 634Pa, the glass transition temperature (Tg) is 152℃, the linear expansion coefficient ɑ1 is 15ppm, the linear expansion coefficient ɑ2 is 54ppm, the DMA modulus at 25℃ is 10545MPa, the DMA modulus at 175℃ is 1642MPa, the DMA modulus at 260℃ is 899MPa, and the continuous molding stability is 705 molds.
[0078] Comparative Example 1 An epoxy resin molding material was prepared according to the method of Example 1, except that the chemical material X1 was replaced by the chemical material DX1 to obtain the epoxy resin molding material D1.
[0079] The epoxy resin molding material D1 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 26s, the fluidity is 52cm, the water absorption is 0.29%, the mold opening strength is 37.22MPa, the mold opening modulus is 860Pa, the glass transition temperature (Tg) is 139℃, the linear expansion coefficient ɑ1 is 17ppm, the linear expansion coefficient ɑ2 is 56ppm, the DMA modulus at 25℃ is 20804MPa, the DMA modulus at 175℃ is 2804MPa, the DMA modulus at 260℃ is 1228MPa, and the continuous molding stability is 460 molds.
[0080] Comparative Example 2 An epoxy resin molding material was prepared according to the method of Example 1, except that the chemical material X1 was replaced by the chemical material DX2 to obtain the epoxy resin molding material D2.
[0081] The epoxy resin molding material D2 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 26s, the fluidity is 62cm, the water absorption is 0.32%, the mold opening strength is 37.05MPa, the mold opening modulus is 834Pa, the glass transition temperature (Tg) is 134℃, the linear expansion coefficient ɑ1 is 17ppm, the linear expansion coefficient ɑ2 is 58pm, the DMA modulus at 25℃ is 21205MPa, the DMA modulus at 175℃ is 3025MPa, the DMA modulus at 260℃ is 1506MPa, and the continuous molding stability is 455 molds.
[0082] Comparative Example 3 An epoxy resin molding material was prepared according to the method of Example 1, except that the linear phenolic resin and the XYLOK phenolic resin were replaced by biphenyl phenolic resin to obtain epoxy resin molding material D3.
[0083] The epoxy resin molding material D3 was tested for gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability. The test results are as follows: The gel time is 27s, the fluidity is 60cm, the water absorption is 0.33%, the mold opening strength is 37.68MPa, the mold opening modulus is 856Pa, the glass transition temperature (Tg) is 137℃, the linear expansion coefficient ɑ1 is 16ppm, the linear expansion coefficient ɑ2 is 58pm, the DMA modulus at 25℃ is 21107MPa, the DMA modulus at 175℃ is 3021MPa, the DMA modulus at 260℃ is 1489MPa, and the continuous molding stability is 451 mold times.
[0084] The gel time, fluidity, water absorption, flame retardancy, mold opening bending strength, mold opening bending modulus, glass transition temperature (Tg), storage modulus, thermal expansion coefficient and continuous molding stability of the epoxy resin molding materials prepared in the above Examples 1-8 and Comparative Examples 1-3 are shown in Table 1 below.
[0085] Table 1
[0086] It can be seen from the results in Table 1 that the epoxy resin molding material prepared according to the method described in the present invention has significantly higher continuous molding stability, better mechanical properties, higher glass transition temperature (Tg), and better fluidity. While maintaining a low water absorption rate, it also has a low room temperature modulus and a high temperature modulus, which can meet the stability of semiconductor devices in the continuous packaging process, reduce costs, and improve the efficiency and reliability of the packaging process.
[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An epoxy resin molding material, characterized in that: Based on the total weight of the epoxy resin molding material, the epoxy resin molding material contains 6-9.5 wt % of epoxy resin, 2-5.5 wt % of a first curing agent, 80-86 wt % of a solid filler, 0.2-0.5 wt % of an ion capture agent, 0.5-0.8 wt % of a low stress modifier, 0.2-0.8 wt % of a coupling agent, 0.1-0.3 wt % of a curing accelerator, 2-5 wt % of a chemical material, 1-2 wt % of a flame retardant and 0.1-0.5 wt % of a colorant; The chemical material is prepared by melt-mixing a second curing agent, an antioxidant and a mold release agent under an inert atmosphere, and based on the total weight of the chemical material, the chemical material contains 70-85% by weight of the second curing agent, 5-15% by weight of the antioxidant and 5-15% by weight of the mold release agent; The first curing agent is a combination of linear phenolic resin and XYLOK phenolic resin, the second curing agent is linear phenolic resin, the antioxidant is a phenolic antioxidant and / or an amine antioxidant, and the release agent is polyethylene wax and / or monoglycerol wax.
2. The epoxy resin molding material according to claim 1, characterized in that: Based on the total weight of the epoxy resin molding material, the epoxy resin molding material contains 6.5-9 weight % of epoxy resin, 2-4.5 weight % of a first curing agent, 80-85 weight % of a solid filler, 0.2-0.4 weight % of an ion capture agent, 0.5-0.7 weight % of a low stress modifier, 0.2-0.6 weight % of a coupling agent, 0.15-0.3 weight % of a curing accelerator, 2.5-4.5 weight % of a chemical material, 1.5-2 weight % of a flame retardant and 0.2-0.5 weight % of a colorant.
3. The epoxy resin molding material according to claim 1 or 2, characterized in that: Based on the total weight of the chemical material, the chemical material contains 75-85 wt % of the second curing agent, 7-15 wt % of the antioxidant and 7-15 wt % of the release agent.
4. The epoxy resin molding material according to any one of claims 1 to 3, characterized in that: In the first curing agent, the mass ratio of the linear phenolic resin to the XYLOK phenolic resin is 1-3:
1.
5. The epoxy resin molding material according to any one of claims 1 to 3, characterized in that: The solid filler is a combination of crystalline silica and fused silica; Preferably, the mass ratio of the crystalline silica to the molten silica is 8-15:
1.
6. The epoxy resin molding material according to any one of claims 1 to 5, characterized in that: The curing accelerator is triphenylphosphine and / or 2-phenyl-4-methylimidazole; and / or The epoxy resin is o-cresol type epoxy resin and / or dicyclopentadiene type epoxy resin; and / or The ion capture agent is at least one of an anion capture agent, a cation capture agent, an anion-cation capture agent and a hydrotalcite compound; and / or The low stress modifier is at least one of an organosilicon-modified epoxy resin, a silicone resin and a triblock copolymer containing an organosilicon component; and / or The coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane; and / or The flame retardant is at least one of a halogen flame retardant, a halogen-free flame retardant, a phosphorus flame retardant, a nitrogen flame retardant and a hydroxide flame retardant; and / or The colorant is carbon black.
7. A method for preparing the epoxy resin molding material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) Under an inert atmosphere, melt-mixing a second curing agent, an antioxidant and a release agent to obtain a chemical material; (2) Melting and kneading the chemical material with epoxy resin, a first curing agent, a solid filler, an ion scavenger, a low stress modifier, a coupling agent, a curing accelerator, a flame retardant and a colorant.
8. The method according to claim 7, characterized in that In step (1), the melt mixing conditions include: temperature of 150-170°C and time of 30-120 min.
9. The method according to claim 7, characterized in that: In step (2), the melt mixing conditions include: temperature of 75-85°C and time of 7-9 minutes.
10. Use of the epoxy resin molding material according to any one of claims 1 to 6 in a semiconductor chip packaging process.